2019
DOI: 10.1021/acs.molpharmaceut.9b00106
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Oligomerization Memory Effects and Their Impact on the Physical Stability of the GLP-1 Agonist Liraglutide

Abstract: Peptides and proteins commonly have complex structural landscapes allowing for transformation into a wide array of species including oligomers, aggregates, and fibrils. The formation of undesirable forms including aggregates and fibrils poses serious risks from the perspective of drug development and disease. Liraglutide, a GLP-1 agonist for the treatment of diabetes, is a conjugated peptide that forms oligomers that can be stabilized by pH and organic solvents. We have developed an analytical toolkit to overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Because of these benefits, lipid modifications of GLP-1 analogues have been reported. Backing up the findings herein, Liraglutide (Victoza), a GLP-1­(7–37;K34R) peptide, incorporating a different lipid moiety (palmitic acid conjugated to Lys26 through a glutamate linker), has also been demonstrated to form fibrils in solution …”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Because of these benefits, lipid modifications of GLP-1 analogues have been reported. Backing up the findings herein, Liraglutide (Victoza), a GLP-1­(7–37;K34R) peptide, incorporating a different lipid moiety (palmitic acid conjugated to Lys26 through a glutamate linker), has also been demonstrated to form fibrils in solution …”
Section: Resultssupporting
confidence: 59%
“…Backing up the findings herein, Liraglutide (Victoza), a GLP-1(7−37;K34R) peptide, incorporating a different lipid moiety (palmitic acid conjugated to Lys26 through a glutamate linker), has also been demonstrated to form fibrils in solution. 37 In addition, the nanostructures formed by C-S and S were assessed by TEM (Figure 4). The results demonstrated that both S and C-S individually aggregated and formed nanofibrils, which further aggregated to yield nanofibers of approximately 200 nm width (Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…16,18,19 Early molecular events such as conformational changes and oligomer formation can predispose peptides to fibrillation later. 20 Detection of these early instabilities through additional biophysical methods may inform formulation optimization, accelerate the selection of fibrillation-resistant peptide candidates and formulations, and reduce the risk of costly late-stage failures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…50,51 At present, there are still some difficulties and challenges in the preparation and application of GLP-1 RA-loaded microspheres. For example, GLP-1 RAs are sensitive to changes in the pH environment, which may lead to aggregation and fibrillation, 52,53 and at the same time, their peptide aminebased structure is prone to acylation reactions with polymer materials causing immunogenicity. So the stability and safety of the peptide after being encapsulated need more attention.…”
Section: Introductionmentioning
confidence: 99%